The Routledge companion to feminism and postfeminism - Gamble, Sarah (Routledge, 2001)
Approachable for general readers as well as for students in women's studies related courses at all levels, this invaluable guide follows the unique Companion format in combining over a dozen in-depth background chapters with more than 400 A-Z dictionary entries. The background chapters are written by major figures in the field of feminist studies, and include thorough coverage of the history of feminism, as well as extensive discussions of topics such as Postfeminism, Men in Feminism, Feminism and New Technologies and Feminism and Philosophy. The dictionary entries cover the major individuals and issues essential to an understanding both of feminism's roots and of the trends that are shaping its future. Readers will find entries on people such as Aphra Behn, Simone de Beauvoir, Princess Diana, Courtney Love and Robert Bly, and on subjects such as Afro-American feminism, cosmetic surgery, the 'new man', prostitution, reproductive technologies and 'slasher' films.